2007
DOI: 10.1074/jbc.m701721200
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-receptive Major Histocompatibility Complex Class I Molecules Cycle between Endoplasmic Reticulum and cis-Golgi in Wild-type Lymphocytes

Abstract: Prior to binding to a high affinity peptide and transporting it to the cell surface, major histocompatibility complex class I molecules are retained inside the cell by retention in the endoplasmic reticulum (ER), recycling through the ER-Golgi intermediate compartment and possibly the cis-Golgi, or both. Using fluorescence microscopy and a novel in vitro COPII (ER-to-ERGolgi intermediate compartment) vesicle formation assay, we find that in both lymphocytes and fibroblasts that lack the functional transporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 83 publications
3
76
0
Order By: Relevance
“…When we co-expressed b 2 m with the K b heavy chains, we observed that wild-type K b now exited the ER but accumulated in the p58-positive compartment (Fig. 7E, bottom left, arrows), indicating that it was retained there by the ERGIC and cis-Golgi quality control (Garstka et al, 2007). Small amounts were detected at the cell surface.…”
Section: Research Articlementioning
confidence: 94%
See 2 more Smart Citations
“…When we co-expressed b 2 m with the K b heavy chains, we observed that wild-type K b now exited the ER but accumulated in the p58-positive compartment (Fig. 7E, bottom left, arrows), indicating that it was retained there by the ERGIC and cis-Golgi quality control (Garstka et al, 2007). Small amounts were detected at the cell surface.…”
Section: Research Articlementioning
confidence: 94%
“…Radiolabeling and immunoprecipitation were performed as described previously (Fritzsche and Springer, 2013). Immunofluorescence microscopy was performed as described previously (Garstka et al, 2007).…”
Section: Cell Lines Reagents and Methods Using Live Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-PLC, MHC I molecules are exported from the ER via a selective process, involving trafficking motifs in the HC cytoplasmic tails and Bap31, which facilitates recruitment into COP-II coated vesicles (31)(32)(33)(34)(35)(36). A bottleneck in the MHC I pathway appears to occur before the medial Golgi with the transport of suboptimally loaded MHC I molecules and PLC components blocked at this step (4,(37)(38)(39)(40). Our most intriguing finding is the ability of TAPBPR to stay associated with MHC I beyond the ER/cis-Golgi, a function that clearly sets TAPBPR apart from all other known components of the MHC I presentation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In cell-based assays, tapasin leads to the increased surface expression, thermostability, and persistence of class I-peptide complexes [4,[7][8][9], but some reports state that it does not influence the composition of the peptide pool bound to class I [10,11]. In assays that use whole cells, the peptide editing function of tapasin may be obscured by ER/Golgi quality control [12], a role of tapasin in the trafficking of class I to or from the Golgi apparatus (Springer et al, unpublished data) [13,14], class I loading by alternative pathways [2], and the metabolic stabilization of TAP by tapasin [3]. In search of the molecular mechanism of peptide editing, several groups have therefore established in vitro assays for tapasin function.…”
Section: Introductionmentioning
confidence: 99%